2011
DOI: 10.4317/medoral.17224
|View full text |Cite
|
Sign up to set email alerts
|

Burning mouth syndrome: Correlation of treatment to clinical variables of the disease

Abstract: Objective: Burning mouth syndrome (BMS) is a complex disorder with a still uncertain etiopathogenesis. A number of treatments have been used in application to BMS, though without clearly successful results. The present study compares the improvement in BMS obtained as a result of different treatment modalities in relation to the clinical characteristics of the patients. Study Design: A retrospective cohort study was made of 115 patients with BMS (109 females and 6 males) subjected to different treatments with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
5
20
0
1
Order By: Relevance
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 89%
“…This study also confirmed the associated symptoms by both groups, i.e., the main symptom in one group appears as an associated symptom in the other group, and vice-versa (4,7,8,15,23,24) . The diversity of symptoms found and associated to the main symptoms -burning sensation and dry mouth -probably makes it difficult to discover the cause, which, as a consequence, results in various treatments (14,18,19,23) .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations